The Effectiveness of the Value Clarification Technique (VCT) Learning Model As An Effort To Internalization Entrepreneur Values at Alfa Centauri Junior High School - Ridho Mujahid Islahi; Neiny Ratmaningsih; Mina Holilah (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
This study examines the effectiveness of the Value Clarification Technique (VCT) learning model in internalizing entrepreneurial character values among students at Alfa Centauri Junior High School. VCT was implemented to strengthen students’ awareness of seven core values through reflective discussion, value-based decision-making, and consistent practice in learning activities. A quantitative method was employed using pretest–posttest assessments and observations involving a sufficient number of student respondents. Data were analyzed using the Wilcoxon Signed Rank test to determine overall effectiveness and N-Gain analysis to measure improvement levels. The results showed a significant increase in students’ understanding and application of entrepreneurial values, with the most notable progress occurring among students with moderate initial value comprehension. Behavioral indicators such as discipline, politeness, and helpfulness also showed improvement. Overall, the study concludes that VCT is effective in enhancing entrepreneurial value internalization, although longer and continuous implementation is required for stronger behavioral impact.